Diffusion and stresses : proceedings of the International Workshop on Diffusion and Stresses, Lillafüred, Hungary, September 19-22, 2006 - Beke, D. L. (Dezső L.); Erdélyi, Z. (Zoltán); Szabó, I. A. (Diffusion and defect data. Defect and diffusion forum, 2007)
The question of the interrelationship between diffusion and stress is almost as old as the investigation of diffusion itself. Nowadays, the study of various diffusion and solid-state reaction processes in thin films and multilayers is a vital area of research activity in which, inevitably, diffusion-induced or thermal stresses are of primary importance. This timely book covers all aspects of the interrelationship between stresses and diffusion phenomena occurring in bulk solids, thin films and multilayered materials and also those which take place at surfaces and interfaces. Such stress-effects are increasingly important at the nanoscale, and the topics covered are fully related to recent progress made in in the field and to the further challenges which are yet to be met.